Strategi Implementasi Manajemen Operasi Dan Manajemen Pemasaran Digital Bagi Peserta Pelatihan Kewirausahaan Di Balai Latihan Kerja Jember - Ahmad Sauqi; Diana Dwi Astuti; Tamriatin Hidayah; Hary Sulaksono (STIE Mandala Jember, 2022)
Mandala College of Economics has long collaborated with the Jember Job Training Center (BLK). In early February 2022, a one-month training was held with a focus on training on Entrepreneurship. We saw a very interesting phenomenon from their enthusiasm in pioneering and running a business with enthusiasm and they (trainees) were very enthusiastic about participating in the training and asked a lot of questions and discussions. The core problems of the training participants include: 1. determining the right amount of product to be produced; 2. The increase in the price of feed resulted in an increase in the selling price of the eggs produced; 3. Online merchants have many competitors as well as their consumers who are already good at making direct purchases in marketplaces such as Shopee and Tokopedia; 4. Problems in marketing their services due to the many competitors, especially in the world of servicing motorcycles, cellphones, computers and so on. The results of this service include entrepreneurship training participants who have been able to apply the Monte Carlo technique, are able to calculate whether to buy or make related feed, have understood the importance of cooperation and strategies to shorten distribution channels in order to get a relatively cheap price, and finally the trainees have been able to apply personal selling and implementing excellent service for their customers, this is evident from the increase in their sales.